(untitled) (Research, Society and Development, 2020)
Teeth absence in the anterior region of the maxilla can lead to psychosocial impairments, especially in young patients. Thus, the treatment of congenital agenesis of upper lateral incisors should consider prosthetic, restorative, and periodontal approaches to recover the patient’s social and aesthetic functions. This article aims to present the case report of a 23-year-old male patient, who visited the Prosthodontic Clinic of the Piracicaba Dental School for the treatment of congenital agenesis of teeth 12 and 22. Implant-supported metal-free ceramic crowns, homemade dental bleaching, and restoration of maxillary canines with composite resin were planned. In addition, to improve gingival thickness around the peri-implant region of tooth 12, a periodontal surgery was performed using the vestibular tunnel access surgical technique (VISTA - Vestibular Incision Subperiosteal Tunnel Access). Thus, a multidisciplinary approach in the treatment of congenital agenesis of the upper lateral incisors has proved to be a reliable alternative to achieve patient’s functional and aesthetic demands.